Policy centers and knowledge mobilization in the field of education in Argentina - Jorge M. Gorostiaga; Mariano I. Palamidessi; Claudia M. Aberbuj (Arizona State University, 2018)
This article describes the processes of production and mobilization of educational knowledge by two policy centers in Argentina during the decade of 2000. It is framed by the theoretical discussions about the use of knowledge in the processes of generating public policies, and about the role of think tanks. The two selected cases are analyzed in relation to the definition of their thematic agendas; the financing and formation of their work teams; their strategies for knowledge production and mobilization; and the (dis)continuities with the action of policy centers in the 1990s.